2021
DOI: 10.1111/dth.15161
|View full text |Cite
|
Sign up to set email alerts
|

Dapsone in hidradenitis suppurativa: A case series of 56 patients

Abstract: Hidradenitis suppurativa (HS) is a chronic inflammatory disease with a challenging treatment. Current guidelines reserve dapsone as a third line agent for patients with mild to moderate HS. To our knowledge, only four small case series have been reported. The objective of this study was to assess the effectiveness and safety of dapsone in our clinical practice. A retrospective observational single-center study of 56 HS patients who underwent treatment with dapsone from May 1, 2015, to June 1, 2021, was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Some patients responded to a lower dose while others required a relatively higher dose. The studies by Murray et al [24] and Lopez-Llunell et al [35] did not show any significant treatment response with dapsone. One study reported the need for maintenance dosage therapy to sustain positive patient outcomes [31].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Some patients responded to a lower dose while others required a relatively higher dose. The studies by Murray et al [24] and Lopez-Llunell et al [35] did not show any significant treatment response with dapsone. One study reported the need for maintenance dosage therapy to sustain positive patient outcomes [31].…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, the effects of the adverse events on treatment outcomes were not significant in most cases. However, adverse events such as headache and nausea did result in the discontinuation of dapsone therapy [24,32,35], as well as the deterioration of the condition only in three patients. Concerns over the safety and side effects of dapsone can sometimes lead to dose reductions and shorter duration of drug administration, both of which can affect its effectiveness.…”
Section: Drug Safetymentioning
confidence: 94%
“…Although it is considered to be a third-line option, dapsone is an antineutrophilic and antieosinophilic antibiotic that is also a possibility for those with mild-to-moderate HS without a G6PD deficiency [ 31 , 32 ]. A 2021 retrospective study features 56 patients with mostly mild to moderate disease and were prescribed 50–150 mg/day of dapsone.…”
Section: Reviewmentioning
confidence: 99%
“…A total of 62.5% of patients achieved HiSCR50 after 12 weeks of treatment. Analysis from the study also identifies an association between tract presence and non-response risk [ 31 ]. These results support dapsone as a treatment for patients with mild to moderate HS that have not developed fistulas or sinus tracts.…”
Section: Reviewmentioning
confidence: 99%
“…It can be used alone or in combination with isotretinoin or surgical techniques. 8 Patients with stage disease III and/or inadequate response to previous treatments could take benefit from TNF-alpha antagonists. The most used agent has been adalimumab.…”
Section: T a B L E 1 Treatment Outcome And Adverse Effectsmentioning
confidence: 99%